ANALISIS PERTUMBUHAN DAN DAYA SAING SEKTORAL KABUPATEN ROKAN HILIR - Tri Azrul Disyamto; Syaiful Hadi; Fajar Restuhadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Demanding regional autonomy regional governments to further optimize the potential to be developed as a sector owned potential . Rokan Hilir regency as one division has a big opportunity in developing the potential of the area owned in order to support the economic development of Rokan Hilir. This study aims to determine the base sector, competitive and growth profile Rokan Hilir area. This study uses secondary data Gross Domestic Product ( GDP ) from the central statistical agency of Riau Province. The analysis used in this study is the analysis of location quotient, shift share analysis, and analysis of growth profiles. The results of this study indicate that the dominant sector in the sector that has the criteria base, the competitive sector, and the sector forward and growing rapidly, that is fisheries sub-sector at constant prices data with the oil and gas, as well as trade, plantation crops sub-sector and sub-sector and the large trade retail at constant price data without gas.   Keywords : Competitive sector , growth profile and sector base